Internationalization Strategy for SMEs thru SWOT and PESTEL Analysis: A Case Study of PT Mujnah Kemiri Lombok - Khusnia, Rif’atul; Sudarmiatin Sudarmiatin; Heri Pratikto (Jurnal Manajemen Bisnis Digital Terkini, 2026)
This study aims to analyze the internationalization strategy of SMEs through the integration of SWOT and PESTEL analysis, using a case study of PT Mujnah Kemiri Lombok. SMEs play an important role in the national economy; however, in the process of expanding into international markets, they face various challenges from both internal and external factors that need to be comprehensively identified. Therefore, a strategic analysis is required to understand the factors influencing the success of internationalization. This study employs a qualitative approach with a case study method. Data were collected through in-depth interviews, observations, and documentation related to the export activities of PT Mujnah Kemiri Lombok. Data analysis was conducted by identifying internal factors using SWOT analysis (Strengths, Weaknesses, Opportunities, Threats) and external factors using PESTEL analysis (Political, Economic, Social, Technological, Environmental, and Legal). The results show that the internationalization process of PT Mujnah Kemiri Lombok occurs gradually, starting from the domestic market and expanding into export markets through technological transformation and network expansion. The company’s main strengths lie in its supply chain network, business experience, and adoption of production technology, while its main weakness is the adaptation of human resources to technological changes. From an external perspective, government support acts as a key driving factor, while global price competition and logistics costs remain major challenges. This study is expected to provide both theoretical and practical contributions, particularly for SMEs in formulating appropriate internationalization strategies and enhancing competitiveness in the global market.